2020
DOI: 10.1111/jcmm.15965
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequence analysis of dermal papilla cells’ regeneration in 3D culture

Abstract: It is well known that dermal papilla cells (DPCs) are crucial for hair follicle growth and regeneration. However, dermal papilla cells in 2D culture could lose their ability of regeneration after several passage intervals. As opposed to DPCs in 2D culture, the DPCs in 3D culture could passage extensively. However, the molecular mechanisms of DPCs’ regeneration in 3D culture remain unclear. Accordingly, gene sequencing is recommended for the investigation of hair regeneration between 2D and 3D culture, the thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Some studies have shown that 3D spherical culture could partially restore the full transcriptional characteristics of DPCs [59] , [60] . In 2021, Zhang et al compared the AGA-related genes and pathways between 2D and 3D cultured DPCs with DHT treatment under high-flux RNA-Seq, and uncovered 501 overlapping DEGs, 10 key genes, chemokines, and related pathways in DPCs cultured in the two models, indicating that chemokines and IL-17 pathways may be related to AGA.…”
Section: Application Of Omics Technologies To the Study Of Agamentioning
confidence: 99%
“…Some studies have shown that 3D spherical culture could partially restore the full transcriptional characteristics of DPCs [59] , [60] . In 2021, Zhang et al compared the AGA-related genes and pathways between 2D and 3D cultured DPCs with DHT treatment under high-flux RNA-Seq, and uncovered 501 overlapping DEGs, 10 key genes, chemokines, and related pathways in DPCs cultured in the two models, indicating that chemokines and IL-17 pathways may be related to AGA.…”
Section: Application Of Omics Technologies To the Study Of Agamentioning
confidence: 99%
“…Dermal papilla cells cultured in 3D regain their ability to induce HF formation, unlike those cultured in 2D. However, the mechanisms underlying this phenomenon are still unclear ( Lin et al, 2020c ). Recently, Lin et al found that Xist, Shh and Shh-associated genes (e.g., Gli family zinc finger 1 and 2) were upregulated, while miRNA-424 was downregulated, in 3D DPC cultures.…”
Section: Roles Of Non-coding Rnas In Specific Parts Of the Hair Folliclementioning
confidence: 99%